eCM 2021
DOI: 10.22203/ecm.v041a29
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial-derived short-chain fatty acids and bone: a potential role in fracture healing

Abstract: Bone healing complications such as delayed healing or non-union affect 5-10 % of patients with a long-bone fracture and lead to reduced quality of life and increased health-care costs. The gut microbiota and the metabolites they produce, mainly short-chain fatty acids (SCFAs), have been shown to impact nearly all organs of the human body including bone. SCFAs show broad activity in positively influencing bone healing outcomes either by acting directly on cell types involved in fracture healing, such as osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 125 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…In a novel study, researchers found that Bacteroides and Rikenellaceae may be involved in bone metabolism and fracture risk (Ozaki et al, 2021). In addition, metabolites of gut microbiota, such as short‐chain fatty acids, have been shown to promote fracture healing by reducing inflammation and inducing bone tissue regeneration (Wallimann et al, 2021). Investigators believed that gut microbes affect bone primarily through three mechanisms, namely regulation of nutrient absorption, stimulation of the immune system and translocation of microbes or microbe‐associated molecules across the endothelial barrier (Castaneda et al, 2020; Hernandez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a novel study, researchers found that Bacteroides and Rikenellaceae may be involved in bone metabolism and fracture risk (Ozaki et al, 2021). In addition, metabolites of gut microbiota, such as short‐chain fatty acids, have been shown to promote fracture healing by reducing inflammation and inducing bone tissue regeneration (Wallimann et al, 2021). Investigators believed that gut microbes affect bone primarily through three mechanisms, namely regulation of nutrient absorption, stimulation of the immune system and translocation of microbes or microbe‐associated molecules across the endothelial barrier (Castaneda et al, 2020; Hernandez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate supplementation enhances the production of 5-Hydroxyindole-3-acetic acid (HIAA), an AhR ligand that programs B cells to become Bregs which mitigate inflammatory arthritis ( Rosser et al, 2020 ). Also, SCFAs can positively influence bone healing process by regulating the activity of bone cells and thus can be employed for fracture healing ( Wallimann et al, 2021 ). Collectively, all these studies clearly establish that SCFAs supplementation can be exploited as a potential therapeutics for the management of various bone pathologies including osteoporosis, fractures and RA.…”
Section: Nexus Between Gut Microbiota and Bone Healthmentioning
confidence: 99%
“…The gut microbiota can play an essential role in bone homeostasis by regulating the production of SCFAs and other metabolites ( Figure 2 ) [ 57 , 76 ]. SCFAs are organic fatty acids with two to six carbon atoms, mainly including acetic acid, propionic acid, butyric acid, etc., [ 77 ]. SCFAs are metabolites produced by the interaction between diet and gut microbiota and are considered to be a key link between gut microbiota and bone [ 44 , 77 ].…”
Section: Gut Microbiota and Bone Metabolismmentioning
confidence: 99%
“…SCFAs are organic fatty acids with two to six carbon atoms, mainly including acetic acid, propionic acid, butyric acid, etc., [ 77 ]. SCFAs are metabolites produced by the interaction between diet and gut microbiota and are considered to be a key link between gut microbiota and bone [ 44 , 77 ]. Gut microbiota can promote the intestinal absorption of nutrients by regulating the production of SCFAs.…”
Section: Gut Microbiota and Bone Metabolismmentioning
confidence: 99%